2020
DOI: 10.3390/ijerph17093259
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Care: Ecological Study for the Evaluation of Completeness and Accuracy in Nursing Assessment

Abstract: Nursing documentation is an important proxy of the quality of care, and quality indicators in nursing assessment can be used to assess and improve the quality of care in health care institutions. The study aims to evaluate the completeness and the accuracy of nursing assessment, analyzing the compilation of pain assessment and nutritional status (body mass index (BMI)) in computerized nursing records, and how it is influenced by four variables: nurse to patient ratio, diagnosis related group weight (DRG), seni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Lindo et al (2016) [ 23 ] reported that more than 60% of the health records audited in three Jamaican hospitals did not include complete nursing assessment data. Iula et al (2020) [ 24 ] indicated that assessments about pain and nutritional status were missing in a sample of 12,513 clinical records that were audited in an Italian hospital. Others show a failure to complete records with instruments that assess functional capacity, falls or pressure ulcers [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lindo et al (2016) [ 23 ] reported that more than 60% of the health records audited in three Jamaican hospitals did not include complete nursing assessment data. Iula et al (2020) [ 24 ] indicated that assessments about pain and nutritional status were missing in a sample of 12,513 clinical records that were audited in an Italian hospital. Others show a failure to complete records with instruments that assess functional capacity, falls or pressure ulcers [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“… 8 9 The purpose of nursing assessment is to let nurses perceive the emotional changes of patients in advance, quickly identify the symptoms of depression of patients, and lay a foundation for the formation of nursing diagnosis and nursing plan. 36 In addition, it can promote multidisciplinary collaboration and provide a basis for further detailed assessment and intervention by physicians. At present, the Hamilton Depression Scale is the most widely used assessment tool in clinical practice or research.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses, as health professionals who have the longest contact time with patients, should make full use of their work advantages, pay attention to observe the psychological state of patients and identify depressive symptoms, especially in patients with acute ischaemic stroke 8 9. The purpose of nursing assessment is to let nurses perceive the emotional changes of patients in advance, quickly identify the symptoms of depression of patients, and lay a foundation for the formation of nursing diagnosis and nursing plan 36. In addition, it can promote multidisciplinary collaboration and provide a basis for further detailed assessment and intervention by physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Nursing documentation should reliably represent nursing care (Paterson et al, 2021); however, it cannot realistically capture the nurse's whole role. Complexities in accurate documentation include issues such as time constraints and competing care priorities, compounded by the fact that documentation is inherently biomedically based and often does not accurately capture the holistic care that nurses provide (Charalambous & Goldberg, 2016; de Marinis et al, 2010; Iula et al, 2020; Johnson et al, 2018; Kebede et al, 2017). Therefore, nursing documentation is inadequate to represent all the complexities of the nursing process (assessment, planning, implementation and evaluation), critical thinking, decision‐making; and time spent monitoring and communicating in, and between clinical teams (Bail et al, 2021; Clarke et al, 2010; de Marinis et al, 2010; Fore et al, 2019).…”
Section: Introductionmentioning
confidence: 99%